2017
DOI: 10.1002/2016jd026025
|View full text |Cite
|
Sign up to set email alerts
|

The role of the meridional sea surface temperature gradient in controlling the Caribbean low‐level jet

Abstract: The Caribbean low‐level jet (CLLJ) is an important modulator of regional climate, especially precipitation, in the Caribbean and Central America. Previous work has inferred, due to their semiannual cycle, an association between CLLJ strength and meridional sea surface temperature (SST) gradients in the Caribbean Sea, suggesting that the SST gradients may control the intensity and vertical shear of the CLLJ. In addition, both the horizontal and vertical structure of the jet have been related to topographic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(93 reference statements)
0
7
0
1
Order By: Relevance
“…In all cases, the HadG shows the poorest results in term of correlation and standard deviation because of an underestimation of the annual mean SST over the region (Martin and Schumacher, 2011), which can affect the structure of the zonal wind patterns, or because the cumulus parameterization affects the low‐level circulation. In addition, land‐sea thermal contrast is better represented in a high‐resolution model and this can also contribute to the RCM's better results (Cook and Vizy, 2010; Maldonado et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, the HadG shows the poorest results in term of correlation and standard deviation because of an underestimation of the annual mean SST over the region (Martin and Schumacher, 2011), which can affect the structure of the zonal wind patterns, or because the cumulus parameterization affects the low‐level circulation. In addition, land‐sea thermal contrast is better represented in a high‐resolution model and this can also contribute to the RCM's better results (Cook and Vizy, 2010; Maldonado et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The convective inhibition is mainly due to the climatology wind shear distribution. This shear as pointed out by [67] is not explained by the observed meridional sea surface temperature gradient, so baroclinicity can be ruled out as opposed to the African Easterly Jet [68] showed that the CLLJ is barotropically unstable in that region [22], so energy could be exchanged between mean flow and disturbances. The CLLJ entrance is observed in the easternmost part of the CS, where descending motion dominates and precipitation is a regional minimum [23,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, the possible summer connections between the CLLJ and the MJO, and their dynamical mechanisms at sub-monthly timescale are yet to be explored. Fluctuations in the intensity of the CLLJ have been suggested to be modulated by the SST gradient between the tropical Pacific and the Caribbean Sea-Atlantic domain (Enfield and Alfaro 1999;Small et al 2007;Wang 2007;Martinez-Sanchez and Cavazos 2014;Fuentes-Franco et al 2015), although this is a current debate (e.g., Maldonado et al 2017). The CLLJ has been observed to strengthen when the inter-basin SST gradient increases (with a warmer-Pacific and cooler-Atlantic configuration), however, Whyte et al 2008 found out that the spatial pattern of the CLLJ intensification depends on which specific basin is primarily modulating the temperature gradient.…”
Section: Sensitivity Analysis To the Mjo And Ensomentioning
confidence: 99%